Prediction value of serum TMAO on myocardial injury after PCI in patients with coronary heart disease based on decision curve analysis - CHEN Guixiu，GUO Cheng，HE Lin (Zhongguo linchuang yanjiu)
Objective To explope the predictive efficacy of serum trimethylamine N ⁃ oxide（TMAO）on myocardial injury after percutaneous coronary intervention（PCI）in patients with coronary heart disease. Methods A total of 200 patients with coronary heart disease who received PCI in Nanchong Central Hospital from June 2020 to June 2023 were selected and divided into myocardial injury group and non⁃myocardial injury group according to whether myocardial injury occurred within 3 months after PCI. The clinical data and serum TMAO levels of the two groups were compared，and the influencing factors of myocardial injury in patients with coronary heart disease after PCI were analyzed by logistic regression. Pearson correlation was used to analyze the correlation between serum TMAO and serum creatine kinase⁃myocardial band（CK⁃MB）and cardiac troponin I（cTnI）. Receiver operating characteristic（ROC）curve was used to analyze the predictive value of serum TMAO on myocardial injury in patients with coronary heart disease after PCI，and R language was used to draw the decision curve. Results During the 3⁃month follow⁃up，7 patients（3.50%）of the 200 patients with coronary heart disease were lost to follow⁃up，4 patients（2.00%）dropped out of the study，and 40 patients（21.16%）of the remaining 189 patients had myocardial injury. There were statistical differences in age，type of coronary heart disease，preoperative statin loading，serum CK⁃MB，serum cTnI and serum TMAO between the myocardial injury group and the non⁃myocardial injury group（P < 0.01）. Multivariate logistic regression analysis showed that old age，unstable coronary heart disease，no preoperative statin loading，elevated serum CK⁃MB level，elevated serum cTnI and elevated serum TMAO were all risk factors for myocardial injury in patients with coronary heart disease after PCI（P < 0.05）. Pearson correlation results showed that serum TMAO level was positively correlated with serum CK⁃MB and cTnI levels in patients with coronary heart disease（P < 0.05）. ROC curve results showed that the area under the curve of serum TMAO in predicting myocardial injury was 0.880（95%CI：0.814-0.945），the sensitivity was 85.7%，and the specificity was 80.3%. The decision curve showed that the net return rate was > 0.26，and the threshold of high risk was 0- 1.0，which had clinical significance. When the threshold being 0.4- 0.7，serum TMAO could effectively predict myocardial injury in patients with coronary heart disease after PCI. Conclusion Serum TMAO can be used as an effective index to predict myocardial injury in patients with coronary heart disease after PCI. In addition，age，type of coronary heart disease，preoperative loading dose of statin，serum CK⁃MB，serum cTnI，serum TMAO and other factors were associated with myocardial injury in patients with coronary heart disease after PCI.